The larva of Wormaldia asterusia Malicky 1972 (Trichoptera: Philopotamidae) with notes on its ecology and an update on the Wormaldia of Greece with a larval key for species of the genus - Karaouzas, Ioannis (Zootaxa, 2016)
The previously unknown larva of Wormaldia asterusia Malicky 1972 is described. The diagnostic features of the species are listed and illustrated and some information on its ecology is included. An update on the knowledge of the genus in Greece is given and a larval key of the known West Palearctic Wormaldia species is provided.